IKLAN PRODUK KECANTIKAN DALAM MAJALAH ELLE - ASIKIN, ANGGITA WULANDEWI (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2017)
ABSTRACT  This research aims at identifying and classifying the kinds of signs and to analyze the meaning and the messages that are found on beauty product advertisements in Elle magazine October 2016 edition. In identifying the kinds of signs in the advertisements, this research uses Peirce’s theory of sign classification that divides signs into three types based on its object, namely index, icon and symbol. In analyzing the meaning of signs and the messages in the advertisements, this research uses Barthes’ theory that identifies types of messages found in illustrated advertisements, namely linguistic messages, uncoded iconic message and coded iconic message in advertisement in finding the meaning and the messages delivered in the advertisements.  The result of this research shows that there are 20 icons, 20 indexes and 8 symbols found in the advertisements, and also each advertisements brings persuasive messages and meanings in order to attract readers. Keywords: sign classification, message in advertisement, beauty product advertisments